Comparative Study On Xylazine, Bupivacaine And Buprenorphine With Ketamine As Lumbosacral Spinal Analgesia In Uremic Buffalo Calves - Pathak, Rekha; Pratap, Krishna; Amarpal (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
36 male buffalo calves aged seven to eight months, weighing 60 to 75 kg were divided into three groups, A, B and C and were used to evaluate the efficacy and safety of lumbosacral spinal analgesia produced by bupivacaine, xylazine and buprenorphine in combination with ketamine respectively in the clinical cases of uremia in buffalo calves with urolithiasis. The onset of analgesia in the animals of group B took place in shortest time (1.75±0.47 min) followed by group C (3.5±0.6 min) and longest time (5.0±0.00 min) was taken by animals of group A . The longest (>180 min.) duration of complete analgesia was recorded in animals of group B. It was concluded that spinal bupivacaine and xylazine when given with ketamine combinations have similar analgesic potency on spinal administration in buffalo calves.